2013
DOI: 10.1007/s40139-013-0012-0
|View full text |Cite
|
Sign up to set email alerts
|

Hitting Them Where They Live: Targeting the Glioblastoma Perivascular Stem Cell Niche

Abstract: Glioblastoma growth potential and resistance to therapy is currently largely attributed to a subset of tumor cells with stem-like properties. If correct, this means that cure will not be possible without eradication of the stem cell fraction and abrogation of those mechanisms through which stem cell activity is induced and maintained. Glioblastoma stem cell functions appear to be non-cell autonomous and the consequence of tumor cell residence within specialized domains such as the perivascular stem cell niche.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 109 publications
(119 reference statements)
0
31
0
Order By: Relevance
“…[8][9][10][11][12] Chemotactic signals from endothelial and other stromal cells and haptotactic signals from the vascular ECM comprise a perivascular niche (PVN) that promotes invasion and resistance to therapy. 5,[13][14][15][16][17] Despite the established role of the PVN in driving rapid dissemination, mechanisms governing the transition from intraparenchymal to perivascular invasion are not well understood. Investigation of local infiltration, vascular homing, and perivascular invasion is made challenging by the absence of advanced culture models.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] Chemotactic signals from endothelial and other stromal cells and haptotactic signals from the vascular ECM comprise a perivascular niche (PVN) that promotes invasion and resistance to therapy. 5,[13][14][15][16][17] Despite the established role of the PVN in driving rapid dissemination, mechanisms governing the transition from intraparenchymal to perivascular invasion are not well understood. Investigation of local infiltration, vascular homing, and perivascular invasion is made challenging by the absence of advanced culture models.…”
Section: Introductionmentioning
confidence: 99%
“…To date, this has been most widely shown in brain tumors, which possess a particularly rich PVN comprising multiple cell types that constitute the blood–brain barrier: astrocytes and often microglia in addition to ECs and pericytes [58–62]. In preclinical models of medulloblastoma, for example, CSCs located within the PVN survive irradiation through several mechanisms including enhanced phosphatidylinositide 3-kinase (PI3K)/v-akt murine thymoma viral oncogene homolog 1 (Akt) signaling [63] or via Yes-associated protein (YAP) expression, which drives insulin-like growth factor 2 (IGF2)/Akt activation [64].…”
Section: Effects Of Pre-existing Tme Properties On Therapeutic Efficacymentioning
confidence: 99%
“…In addition, recent studies [1,44,66] support that vasculogenesis [34,56] by GSCs may occur directly via differentiation of cells that participate in vasculogenesis, tumor growth, or indirectly via cytokines and chemokines production stimulated by hypoxia, which are known to activate endothelial cells. Interestingly, through a three dimensional reconstruction, Calabrese et al demonstrated that brain GSCs are preferentially located in close contact to tumor microvasculature and that endothelial cells release trophic factors that maintain these cells in a selfrenewing and undifferentiated state [12].…”
Section: Glioblastoma Stem Cells and Ykl-40mentioning
confidence: 99%